Sangue e sombras : a memória familiar em Vermelho, de Mafalda Ivo Cruz - Canilha, Samla Borges (2018)
The present study aims to analyse the use of memory, especially of family memory, in the novel Vermelho (2003), from the portuguese writer Mafalda Ivo Cruz. In it, the narrator protagonist, Tito, seeks to recover the genealogy of his family, resulting in a narrative marked by a form that largely reflects the discourse of memory, a theme dear to the author's work. Thus, the theoretical reference used here mainly consists of memory theorists such as Henri Bergson, Maurice Halbwachs, Paul Ricoeur, Aleida Assmann and Jöel Candau. Besides that, we resorted to texts from narratology to support the reading of the novel, especially in what concerns the construction of the narrator. From the analysis performed, one can see that, contrary to what is expected of a memory narrative, that is, an organization of the past in a coherent and temporally linear whole, Tito transmits the family's past into a construction that reflects his disturbed mind. The chaos is also a reflection of the fact that the family history in evidence is full of gaps and silences that are often fictionally filled by its members, especially the manipulation elaborated by Mário, the stepfather, the main responsible for the oral transmission of events to Tito. Ultimately, the objects of the family archive, in addition to being suspected of falsehood, may have been selected arbitrarily to serve the protagonist's purposes. Therefore, the narrator ends by, rather than reconstituting, founding a memory of the family, but the result is problematic, once Tito is not a reliable narrator.